Midtemperature solar systems test faclity predictions for thermal performance based on test data: Solar Kinetics T-700 solar collector with glass reflector surface - Harrison, T.D. (Sandia National Laboratories, 1981)
Sandia National Laboratories, Albuquerque (SNLA), is currently conducting a program to predict the performance and measure the characteristics of commercially available solar collectors that have the potential for use in industrial process heat and enhanced oil recovery applications. The thermal performance predictions for the Solar Kinetics solar line-focusing parabolic trough collector for five cities in the US are presented. (WHK)